Evolution and performance of exchange rate regimes - Rogoff, Kenneth S. (Washington, DC : International Monetary Fund, 2004)
This paper addresses economies and their institutions mautre, the value of exchange rate flexibility increases. The study takes a a given that multiple currencies will continue to exist in the foreseeable future.
Includes bibliographical references (p. 50-53)
osa11/06/13
Loans
Keywords: Foreign exchange rates; Foreign exchange rates -- Developing countries; Inflation (Finance); Business cycles